Analizamos un fragmento de la obra El Ingenioso Hidalgo Don Quijote de la Mancha - Hilario Salvador, Marianela Maritza (2019)
The present lesson Planning has as reference one fragment of the book the ingenious gentleman Don Quijote of La Mancha which Will be analyzed in content (theme, character events with their characteristics)_x000D_ Students will have to analyze and recognize some contents from the book so they could understand and infer the intention of the author. These elements Will be taken during the lesson, to Foster and encourage the love for Reading and also appreciation of Spanish Literature among the students.